2020
DOI: 10.1002/ajp.23138
|View full text |Cite
|
Sign up to set email alerts
|

Low relationship quality predicts scratch contagion during tense situations in orangutans (Pongo pygmaeus)

Abstract: Primates show various forms of behavioral contagion that are stronger between kin and friends. As a result, behavioral contagion is thought to promote group coordination, social cohesion, and possibly state matching. Aside from contagious yawning, little is known about the contagious effect of other behaviors. Scratching is commonly observed during arousal and as such may play a role within group dynamics. While the Bornean orangutan ( Pongo pygmaeus ) is commonly considered the least so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(43 citation statements)
references
References 84 publications
1
37
1
Order By: Relevance
“…For instance, a large study in rats has shown a familiarity bias in the opposite direction with rats being more likely to yawn in response to unfamiliar yawns 23 . Similarly, a recent study investigating scratch contagion in orangutans found that during tense situations, orangutans are more likely to take over scratching from individuals with whom they have a weak bond 80 , indicating a (negative) correlation between social closeness and the contagiousness of a behavior or motor pattern. Thus, it remains possible that social modulation of CY is present in orangutans, at least in those living with conspecifics in captivity, although its presence was not shown in our sample.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…For instance, a large study in rats has shown a familiarity bias in the opposite direction with rats being more likely to yawn in response to unfamiliar yawns 23 . Similarly, a recent study investigating scratch contagion in orangutans found that during tense situations, orangutans are more likely to take over scratching from individuals with whom they have a weak bond 80 , indicating a (negative) correlation between social closeness and the contagiousness of a behavior or motor pattern. Thus, it remains possible that social modulation of CY is present in orangutans, at least in those living with conspecifics in captivity, although its presence was not shown in our sample.…”
Section: Discussionmentioning
confidence: 91%
“…For instance, related female orangutans are known to associate more often than unrelated females 78 , and prefer the long-calls of dominant males 79 . Additionally, in a recent study, orangutans were shown to scratch contagiously in response to conspecifics scratching, suggesting a potential case of emotion contagion 80 . Interestingly, scratch contagion was stronger between weakly bonded individuals during tense situations, which shows a social closeness bias in the opposite direction.…”
Section: Discussionmentioning
confidence: 93%
“…Synchronization is observed on many different levels 9 , in infants 6,28 , and in different species 13,29,30 . Theoretically, it has been proposed to make two interaction partners more similar, aligned, and easier to predict, which is why they are able to cooperate more efficiently 16 .…”
Section: Discussionmentioning
confidence: 99%
“…The vast majority of studies on behavioural contagion focuses on non-interactive activities, such as contagious yawning and itching/scratching [ 13 , 14 ]. Contagious yawning is probably the best-studied example of non-interactive contagious behaviour and may serve to enhance collective vigilance and to facilitate an adaptive response to external stimuli [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The degree of behavioural contagion of non-interactive behaviour is often modulated by relationship quality between the stimulus individual and the bystander. Contagious yawning is enhanced when the triggering individual is a close social partner in geladas ( Theropithecus gelada ), bonobos ( Pan paniscus ) and humans ([ 40 ]; for an opposing effect in contagious scratching, see [ 14 , 21 , 41 ]) or an in-group versus out-group individual in chimpanzees [ 42 ]. Yawn contagion is also facilitated when the triggering individual is of high social status, i.e.…”
Section: Introductionmentioning
confidence: 99%